Decent work: what matters most and who can make a difference?. Issue 4 (9th April 2020) - Gibb, Stephen; Ishaq, Mohammed
Abstract : Purpose: What matters most for improving work quality and who can make a difference are perennial topics in employee relations research. The literature on work quality provides answers to these with regard to various constructs on a continuum from "soft" to "hard" variables and stakeholders seeking to influence employers who fall short of reasonable expectations with regard to these. A construct of "decent work" with both soft and hard variables was adopted for research and methods which were collaborative and participative with stakeholders in one national context. Design/methodology/approach: The "decent work" construct was operationalised from the literature and refined by collaborative and participative research. Exploring the relative importance of the constituent parts of decent work involved research with a range of stakeholders; employees, employers and advocates. The study involved most prominently low-paid workers, with employers and advocates also engaged through interviews. Findings: Primarily hard "decent work" variables were identified among employees, primarily soft variables among employers and a mix of hard and soft among advocates. There are some common priorities across these stakeholders. Research limitations/implications: The main implication is that to engage a range of stakeholders requires a combination of soft and hard variables to be included in research and policy development. However, generalisation about what matters most and who makes a difference to work quality is intrinsically limited in context and time. In this research, the extent of employer engagement in the collaboration initiated by advocates and concerned most with the experiences of low-paid workers is a limitation. Practical implications: What matters most are a set of soft and hard priorities to engage across stakeholders. Pay is an abiding priority among these and the priority most prominent for many advocates seeking to make a difference through influencing low-paying employers to provide a living wage. While the living wage is a significant focus for work quality, it is not in itself sufficient, as other soft and hard variables in the workplace matter as well. Those who can make a difference are the employers falling short of benchmark standards. Influence on these may emerge through decent work knowledge and skills in management and professional development programmes as well as in initiatives advocating wider adoption of the living wage. Social implications: Problem areas of work quality, and problem employers, can be influenced by strategies shaping "hard" factors, including legislation. This needs to be complemented and integrated with strategies on "soft" factors, including identifying positive role models on themes of well-being, work–life balance and precarious forms of employment, as well as pay. Originality/value: The identification of what matters and who can make a difference is based on an original, collaborative, research project, in one national context, offering analytical generalisability about "decent work" and an experience of collaborative research.